TRADITIONAL CULTURE OF THE NORTH CAUCASUS PEOPLES IN CONTEMPORARY SOCIETY - Kanukova, Zalina Vladimirovna (History, Archeology and Ethnography of the Caucasus, 2024)
The interest in the traditional culture of the peoples of the North Caucasus is driven by the increasing public interest in ethnocultural values, which manifests in various expressions within modern society, particularly in the regional segments of the Internet space, and frequently occurs spontaneously. The process of updating traditional culture in all its forms is intriguing, as its study helps to identify the causes, essence, and resources for modernization, as well as to predict its consequences. The article considers commitment to traditional culture as a means of expressing ethnic identity, which remains a determining factor in many aspects of life in the North Caucasus. It also views this commitment as a defensive reaction to the risks posed by the information society, with its vast integration potential and global intercultural communication. Particular attention is given to the actualization of tradition among the younger generation, who are at the forefront of revival practices aimed at preserving and developing their native language and culture. The study reveals that, alongside numerous positive outcomes, there are also consequences related to falsifications and ignorant interpretations of cultural phenomena. These issues are widespread across the network space, various entertainment events, and publishing projects. A barrier to falsifications and provocative projects should be the popularization of scientific knowledge, but in a modern presentation, in the form of a media product. The article proposes an applied project for the creation of a digital database titled “Innovative Resources of the Historical and Cultural Heritage of the Republic of North Ossetia-Alania”. This database aims to present complete, scientifically substantiated, and systematized historical and cultural information on cultural heritage sites. The digital database will include interpretations of key issues, images, symbols, names, and historical and cultural phenomena, all free from ignorance, fanaticism, and false interpretations. This resource will help to determine the meaning and essence of the original tradition, trace the dynamics of its development, and identify potential prospects in modern society. Specifically, it will aid in the development of tourism, the preservation and actualization of folk crafts, and the implementation of socio-cultural, educational, and upbringing projects.